Level of Moral Distress in Operating Room Technologist Students in Iran: A Cross‑Sectional Study - Kamali, Nasrin; Hannani, Sedigheh; Amiri, Fardin; Hosseini, Agha Fatemeh; Mohammadi, Sara (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Moral distress is one of the issues considered in the educational environment. That it can affect the physical, psychological, and social dimensions of individuals and access to ethical and educational goals. This study aimed to investigate the moral distress in operating room technologist students of Iran University of Medical Sciences. Methods: This cross-sectional study was performed on Iran University of Medical Sciences’ operating room technologist students in 2017. Data were collected with two questionnaires, including demographic information and a moral distress questionnaire. Data were analyzed by SPSS software using an independent t-test and one-way ANOVA (P < 0.05). Results: In this study, 121 operating room technologist students participated. The mean score of moral distress in the scores’ severity and frequency dimensions was (3.5 ± 1.76) and (3.11 ± 1.6), respectively. The results showed that only age and semester had a significant relationship with the total score of moral distress, and with increasing age and semester, students’ moral pain has decreased. Conclusions: This study’s results indicated that the moral distress in operating room technologist students was moderate, which requires investigating the factors involved in creating moral distress and providing strategies and measures to reduce its adverse effects in the educational setting.